1998
DOI: 10.1021/bi971969b
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofN-Arginine Dibasic Convertase Activity by Amines:  Putative Role of a Novel Acidic Domain as an Amine Binding Site

Abstract: Peptide sequence analysis and cDNA cloning indicate that a previously described mouse arginine-specific dibasic cleaving enzyme (dynorphin converting enzyme) [Csuhai et al. (1995) Biochemistry 34, 12411] is the homologue of N-arginine dibasic convertase (NRDc) isolated from rat testis [Chesneau et al. (1994) J. Biol. Chem. 269, 2056]. A mouse NRDc cDNA exhibited 98% amino acid identity with the rat cDNA. However, within a 74 residue acidic stretch, this identity drops to 82%. Likewise, the corresponding acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In this way, NRDc might contribute to the dysregulation of dynorphins in AD (Yakovleva et al 2007) and, possibly, to the elevated levels of the isoform somatostatin-28 Winsky-Sommerer et al 2003), which appear in parallel to the well-documented general somatostatin deficit in AD (Rossor et al 1984;Beal et al 1987;Mouradian et al 1991;Dournaud et al 1995). Although there is only little, if any, overlap of NRDc and somatostatin-28 immunoreactive nerve cell bodies in human brain (Bernstein et al 2007), a reduced somatostatin-28 metabolising function of NRDc (Csuhai et al 1998) cannot be ruled out in AD. In addition, NRDc has been demonstrated to interact with p42 IP4 /centaurin-α1 (Stricker et al 2006), which seems to play a role in AD Bernstein 2002, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, NRDc might contribute to the dysregulation of dynorphins in AD (Yakovleva et al 2007) and, possibly, to the elevated levels of the isoform somatostatin-28 Winsky-Sommerer et al 2003), which appear in parallel to the well-documented general somatostatin deficit in AD (Rossor et al 1984;Beal et al 1987;Mouradian et al 1991;Dournaud et al 1995). Although there is only little, if any, overlap of NRDc and somatostatin-28 immunoreactive nerve cell bodies in human brain (Bernstein et al 2007), a reduced somatostatin-28 metabolising function of NRDc (Csuhai et al 1998) cannot be ruled out in AD. In addition, NRDc has been demonstrated to interact with p42 IP4 /centaurin-α1 (Stricker et al 2006), which seems to play a role in AD Bernstein 2002, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this acidic domain might play a role in the regulation of nardilysin activity by forming charge-charge complexes with other cellular components (6,7).…”
mentioning
confidence: 99%
“…Rat, human and mouse cDNA sequences encoding NRD-C have been isolated [14,[18][19][20], and the deduced amino acid sequences have revealed that the enzyme is part of a large family of metalloendopeptidases -the M16 family (using the nomenclature of Rawlings and Barrett [21,22]). Many of the enzymes in this family have been implicated in prohormone or proprotein processing events.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that this acidic stretch might be a target for polyamines, which have been shown to inhibit the binding of rat, mouse and human NRD-C to its substrates and to control the activity of the enzyme [18,34]. It has been reported that expression of the enzyme is modulated by retinoic acid in human neuroblastoma cell lines and that this retinoic acid-responsiveness might be mediated by a retinoic acid-responsive element within the promoter of the NRD-C gene [35].…”
Section: Introductionmentioning
confidence: 99%